Exploration of prescribing error reporting across primary care: a qualitative study - Scott Wilkes; Kathryn Bullen; Nicola Hall; John Sherwood; Nicola Wake; Gemma Donovan (BMJ Open, 2022)
Objectives To explore barriers and facilitators to prescribing error reporting across primary care.Design Qualitative semi-structured face-to-face and telephone interviews were conducted to explore facilitators and barriers to reporting prescribing errors. Data collection and thematic analysis were informed by the COM-B model of behaviour change. Framework analysis was used for coding and charting the data with the assistance of NVivo software (V.12). General and context specific influences on prescribing error reporting were mapped to constructs from the COM-B model (ie, capability, opportunity and motivation).Setting Primary care organisations, including community pharmacy, general practice and community care from North East England.Participants We interviewed a maximal variation purposive sample of 25 participants, including prescribers, community pharmacists and key stakeholders with primary care or medicines safety roles at local, regional and national levels.Results Our findings describe a range of factors that influence the capability, opportunity and motivation to report prescribing errors in primary care. Three key contextual factors are also highlighted that were found to underpin many of the behavioural influences on reporting in this setting: the nature of prescribing; heterogeneous priorities for error reporting across and within different primary care organisations; and the complex infrastructure of reporting and learning pathways across primary care. Findings suggest that there is a lack of consistency in how, when and by whom, prescribing errors are reported across primary care.Conclusions Further research is needed to identify cross-organisational and interprofessional consensus on agreed reporting thresholds and how best to facilitate a more collaborative approach to reporting and learning, that is, sensitive to the needs and priorities of disparate organisations across primary care. Despite acknowledged challenges, there may be potential for an increased role of community pharmacy in prescribing error reporting to support future learning.